Enabling Characteristic LSL (Laki-Laki Seks dengan Laki-Laki) HIV Positif dalam Pemanfaatan Layanan CST (Care Support and Treatment) di Kabupaten Jember - Nur Khamid; Anisah Prafitralia (Jurnal Al-Tatwir, 2020)
HIV-positive MSM are men who engage in same-sex sexual behavior and have been positively diagnosed with HIV. According to Public Health Offices data in Jember, there had been 3.186 cases of HIV and AIDS from 2004 to June 2017, in which homosexual risk factor contributed by 7.6%. The current study aimed at analyzing Enabling Characteristics of HIV-POSITIVE MSM which included the followings: a) Family/individual income, b) Insurance participation and fee, c) Knowledge of HIV-positive MSM community on VCT and CST, and d) Skills of health workers. The current qualitative study employed a case study research approach. There were eight (8) respondents who were determined by means of Purposive sampling technique for the study. In analyzing data, thematic content analysis method was employed. The results of the study revealed that the individual income of most main respondents were 3 (three) millions per month while a few main respondents didn’t have a permanent job so their monthly incomes were uncertain, b) Most of the main respondents didn't apply for any health insurance because they didn't have Family Registration (KK) / Identity Card (KTP) and they were worried about their HIV status being exposed by the Public Health Centers (Puskesmas), c) Main respondents had some knowledge and information on VCT (voluntary counseling & test) and CST (care support & treatment) services which sources vary from health workers, social media and public information signs. In addition, the respondents knew some types of ARV (antiretroviral) from health workers and the internet, d) the respondents also stated that the skills of the health workers were very good, whilst the language used by the health workers were polite, friendly, and they treated patients and officers equally.